2009
DOI: 10.1161/circresaha.109.193805
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin

Abstract: Abstract-The characteristics of dilated cardiomyopathy (DCM) resulting from chronic viral myocarditis are remodeling processes of the extracellular matrix. Based on our findings of enhanced osteopontin (OPN) expression in inflamed human hearts, we further investigated in the murine model of acute and chronic coxsackievirus (CV)B3-myocarditis the role of OPN regarding its involvement in resolution of cardiac virus infection and fibrosis. In hearts of A.BY/SnJ mice susceptible to chronic CVB3-myocarditis, a pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…(35) High expression levels of OPN in acute myocarditis are associated with the development of extensive fibrosis. (36) It was reported that quercetin, an antioxidant flavonoid compound found in ML, normalized the calcium movement in transgenic mouse model. (37) In our study, the myocardial level of SERCA2 was significantly decreased and OPN level was increased in the control rats which was found to be normalized in the ML treated group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(35) High expression levels of OPN in acute myocarditis are associated with the development of extensive fibrosis. (36) It was reported that quercetin, an antioxidant flavonoid compound found in ML, normalized the calcium movement in transgenic mouse model. (37) In our study, the myocardial level of SERCA2 was significantly decreased and OPN level was increased in the control rats which was found to be normalized in the ML treated group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a murine model of viral myocarditis, a vitamin D analog reduced myocardial fibrosis by inhibition of osteopontin expression. 114 The secretion of atrial natriuretic peptide (which influences proliferation) is also suppressed by 1,25(OH) 2 D, although it is unclear whether this plays a role in any antihypertrophic effect. 62 In addition, the expression of type 1 natiuretic peptide receptor-A, an inhibitor of RAS and myocardial hypertrophy, is increased by 1,25(OH) 2 D. 63 The rate and magnitude of cardiomyocyte sarcomere contraction is modulated by 1,25(OH) 2 D via interaction with caveolin-3 in t-tubules.…”
Section: Cardiomyocyte Function and Cardiac Hypertrophymentioning
confidence: 99%
“…PA1/08). Four-week-old mice from two mouse strains (SWR/J (H-2q) and ABY/SnJ (H-2b)) were infected with CVB3 Nancy strain as described previously [12,13]. Non-infected animals of both strains served as controls.…”
Section: Methodsmentioning
confidence: 99%